Effect of Epoxy/Al2O3/CeO2 Coating on Corrosion Rate and Mechanical Properties of Mild Steel - Nasih, M.N.; Vicki, W.V. (International Journal of Engineering and Technology, 2018)
In any industry like a power station, corrosion is a natural process that commonly happens and one of the problems that need to be considered. The example is in the underground pipeline where sea water is transported for cooling purposes. This study mainly on corrosion rate and mechanical properties of coating material on mild steel. Theoretically, Metal can get the higher rate of corrosion when exposed to the surrounding environment. Corrosion can cause to a lot of unwanted conditions, including failures in functions and higher maintenance cost as well as it is too risky for safety. The objective of this project is to study the corrosion rate and mechanical properties of the coating material of pure epoxy, aluminum oxide (Al2O3) and cerium oxide (CeO2) on mild steel. Different composition of epoxy/ Al2O3/CeO2 coating tested on mild steel specimen. There is three experimental conduct which is a Gamry test for corrosion rate and impact and hardness test for mechanical tests. As a conclusion, the results from the tests show that the coated mild steel of Al2O3-CeO2-epoxy obtained the best value in term of corrosion resistance and mechanical properties.